2017
DOI: 10.1177/0960327117705427
|View full text |Cite
|
Sign up to set email alerts
|

Seizures in patients with acute pesticide intoxication, with a focus on glufosinate ammonium

Abstract: The incidence and clinical aspects of seizures remain to be elucidated in patients with acute pesticide intoxication. The present study included subjects who ingested pesticide with the intention of committing suicide and were treated at Soonchunhyang University Hospital (Cheonan, Korea) between January 2011 and December 2014. We analyzed the incidence and characterized the type and frequency of seizure, from the medical records of 464 patients with acute pesticide intoxication, according to the pesticide clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…In this respect, a patient with the most severe symptoms (who also had the most extended hospital and ICU stay days) suffered from a sustained seizure until hospital day 6, whereby there was performed FDG-PET CT 98 days after the seizure stopped. In other patients, the seizure was noted to have stopped within 72 hours after ingestion, similar to our previous report [7], and FDG-PET images were obtained 7-58 days after the seizure had not occurred. Although further research on seizure and glucose hypometabolism, caused by GLA, could help reveal the mechanism of its neurotoxicity, in this study, the effect of seizure on glucose metabolism might not be a significant factor.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In this respect, a patient with the most severe symptoms (who also had the most extended hospital and ICU stay days) suffered from a sustained seizure until hospital day 6, whereby there was performed FDG-PET CT 98 days after the seizure stopped. In other patients, the seizure was noted to have stopped within 72 hours after ingestion, similar to our previous report [7], and FDG-PET images were obtained 7-58 days after the seizure had not occurred. Although further research on seizure and glucose hypometabolism, caused by GLA, could help reveal the mechanism of its neurotoxicity, in this study, the effect of seizure on glucose metabolism might not be a significant factor.…”
Section: Discussionsupporting
confidence: 85%
“…However, there has been no long-term follow-up study in patients with oral pesticide intoxication. Small case series and studies have reported symptoms associated with GLA intoxication, such as loss of consciousness, seizure, irritability, memory impairment, respiratory deterioration, hypotension, hyperammonemia, rhabdomyolysis, and metabolic acidosis [5][6][7]11,25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The causes of death were associated with decreased Glasgow coma scale and bicarbonate, use of mechanical ventilator, and vasopressors 42 . Therefore, the ingestion of a large amount of glufosinate by humans can cause intoxication problems, but the proper use of glufosinate as a herbicide can be considered safe when guidelines are followed 43 …”
Section: Glufosinate Toxicologymentioning
confidence: 99%
“…Glufosinateammonium, which is the best substitute for paraquat, has low toxicity but glufosinate-ammonium poisoning incidents also often occur, causing certain harm to the human respiratory system, digestive system, and nervous system. 10,11 Furthermore, the use of these pesticides has introduced a large number of residues into the soil and drinking water, which will enter the food chain and the human body due to their aquatic use pattern and high environmental stability. Therefore, to monitor these pesticides in agriculture products, soil, and drinking water, the development of simple, rapid, and efficient detection methods is of urgent importance.…”
Section: Introductionmentioning
confidence: 99%